Prediction of financial distress using the altman z-score method: It’s impact on stock prices of companies in the properties and real estate subsector - Rizka Wahyuni Amelia; Lina Nofiana; Achmad Ludvy (Institute of Accounting Research and Novation (IARN), 2025)
This research seeks to asses the precence of Prediction Financial Distress using the Altman Zscore Method: it’s Effect on Stock Prices of Companies in the Properties and Real Estate Subsector Listed on the Indonesia Stock Exchange for the Period 2015-2023. The research method used is quantitative Associative. The data analysis technique used is descriptive statistics and simple and multiple linear analysis using SPSS ver.23. The test results show that all companies in 2015-2019 were in a safe condition but financially vulnerable since 2020-2023 have been in the gray zone even though they are not yet in the acute distress category. The variables Net Working Capital to Total Assets (WCTA), Retained Earning to Total Assets (RETA), Earning Before Interest and Tax to Total Assets (EBITA), Market Value Of Equity to Book Value Of Debt (MVEBVL) and Sales to Total Assets (STA) together do not have a significant effect on stock prices with a significance value of 0.970409 greater than 0.05.